Addressing the role of personality, ability, and positive and negative affect in positive psychology interventions: Findings from a randomized intervention based on the authentic happiness theory and extensions. Issue 6 (1st November 2016) - Proyer, René T.; Gander, Fabian; Wellenzohn, Sara; Ruch, Willibald
Abstract : The present study explores the role of personality, ability, and affect in a randomized, group-based positive psychology intervention program based on Seligman's authentic happiness theory and extensions. A total of 100 adults ( M  = 45.7, SD = 12.8) were randomly assigned to the 12-week intervention program (five training sessions) or a waiting list control group. The intervention consisted of basic information, group activities, and homework assignments. Participants in the intervention group demonstrated higher levels of happiness, pleasure, and engagement after completion of the program. Baseline levels of psychometric intelligence moderated the intervention effectiveness (greater effects for those higher in reasoning, vocabulary, and general intelligence). There were no effects for the big five personality traits. Finally, increases in positive affect before and after the homework assignment were associated with greater levels of happiness after the program. The relevance of these findings for the development of new programs is discussed.